Respon Antibiotik Salmonella typhi pada Anak dengan Demam Tifoid - Febilla Naili Alfalah; Intanri Kurniati; Dian Isti Angraini; Oktadoni Saputra (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Typhoid fever is a significant health issue worldwide, especially in developing countries. The highest incidence of typhoid fever occurs in the pediatric population, particularly among school-age children. Patients often resort to self-medication with antibiotics, where chloramphenicol is the primary choice for treating typhoid fever in Indonesia. However, reports of resistance to the chloramphenicol group have been documented in some locations. A total of 8 articles are included in this literature, revealing the existence of resistant isolates in the antibiotic susceptibility test for Salmonella thypi during the primary therapy. Several cases demonstrate resistance to various antibiotics such as ceftriaxone, cefuroxime, amoxicillin, ampicillin, ciprofloxacin, augmentin, fluoroquinolones, azithromycin, and nalidixic acid. However, some drugs have proven effective, including Cefixime, ceftriaxone, chloramphenicol, ofloxacin, cefepime, quinolones, and third-generation cephalosporins, which are considered sensitive to S. Typhi.